Colocial Expression of Students of SMA Negeri 4 Ambon in Oral Language (Ethnographic Study of Communication) - Carolina Sasabone; Petrus. J. Pattiasina; Merlin Rutumalessy (Budapest International Research and Critics University, 2022)
Language is seen as a science, cannot be separated in interaction between humans and is translated into the scope of education, both formal, non-formal and informal. In social interaction, language functions to convey messages in interaction or conversation. Language is seen from an axiological point of view, then language is a form of human behavior in the dimensions of social life of society which naturally grows and develops in various aspects of human life, especially the association of students in the school environment. In connection with this research, the problem discussed is